Iridium(i) complexes with bidentate NHC ligands as catalysts for dehydrogenative directed C–H silylation. Issue 28 (21st March 2023) - Manguin, Romane; Galiana-Cameo, María; Kittikool, Tanakorn; Barthes, Cécile; Thongpaen, Jompol; Bancal, Etienne; Mallet-Ladeira, Sonia; Yotphan, Sirilata; Castarlenas, Ricardo; Mauduit, Marc; Sortais, Jean-Baptiste; Baslé, Olivier
Abstract : Bidentate NHC-Ir(i ) catalysts for selective dehydrogenative C–H silylation. Abstract : A series of (NHC)(cod)Ir(i ) complexes bearing NHC-carboxylate ligands were efficiently synthesized and fully characterized. Their solid-state structures confirmed the bidentate coordination mode of these LX-type NHC ligands. These unprecedented iridium(i ) complexes demonstrated efficient catalytic activities in dehydrogenative directed C–H silylation of arenes, and allowed for excellent ortho -selectivity control with aromatic silylating agents.